An Emerging Developmental Ecological Psychology: Future Directions and Potentials. Issue 2 (3rd April 2018) - Read, Catherine; Szokolszky, Agnes
ABSTRACT: This article explores the relation of ecological perceptual research on infancy to adult Ecological Psychology, including contrasts between the ideas of invariants for perception and distinctive features that are the basis of perceptual learning. We concentrate on relations between development and learning and go on to elaborate principles of Ecological Psychology (as presented in Michaels & Palatinus, 2014) into developmental principles. As a result of this analysis, we stress that researchers must at least indicate how results relate to the organism-environment system at the level of the organism . We go on to present Goethe's work in morphology that stresses transformation as the key to development as a resource for theorizing and researching organismic development. This approach goes beyond "snapshots" at any one point in time and beyond any simple linear or additive model of change over the life span. We then draw on recent developments in organicism in biology (cf. Gilbert & Sarkar, 2000) to distinguish levels of functioning in living organisms, again with an eye to organismic functioning. Finally, we propose that these various branches of biology are potential resources for a psychology committed to ecology, that is, organism-environment mutuality existing over time and in all settings.